2007
DOI: 10.1103/physrevlett.98.137204
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetic Interactions in Single CrystallineZn1xCoxOThin Films

Abstract: In a rather contradictory situation regarding magnetic data on Co-doped ZnO, we have succeeded in fabricating high-quality single crystalline Zn(1-x)Co(x)O (x=0.003-0.07) thin films. This gives us the possibility, for the first time, to examine the intrinsic magnetic properties of ZnO:Co at a quantitative level and therefore to address several unsolved problems, the major one being the nature of the Co-Co interaction in the ZnO structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
78
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(96 citation statements)
references
References 29 publications
18
78
0
Order By: Relevance
“…Within the LSDA+ U, both the in-plane and out-of-plane magnetic interactions are antiferromagnetic and their strength is more or less independent of the Co cluster size. From magnetic measurements, exchange parameters J in = −21 K and J out = −9 K were reported, 27 which are in good agreement with our LSDA+ U values, especially for the J in / J out ratio. A good consensus exists also with the the- 28 which reported the values of J in = −23 K and J out = −8 K for an isolated pair, with the LSDA+ U approach.…”
Section: A Structural and Magnetic Propertiessupporting
confidence: 74%
“…Within the LSDA+ U, both the in-plane and out-of-plane magnetic interactions are antiferromagnetic and their strength is more or less independent of the Co cluster size. From magnetic measurements, exchange parameters J in = −21 K and J out = −9 K were reported, 27 which are in good agreement with our LSDA+ U values, especially for the J in / J out ratio. A good consensus exists also with the the- 28 which reported the values of J in = −23 K and J out = −8 K for an isolated pair, with the LSDA+ U approach.…”
Section: A Structural and Magnetic Propertiessupporting
confidence: 74%
“…The Weiss temperature of all the samples are negative, consistent with the report of antiferromagnetic interaction in paramagnetic Zn 1−x Co x O thin films. 18 In order to see the effects of vacuum annealing on the electronic and magnetic properties of the Co ion, we have measured the Co 2p XMCD spectra of the P O2 =10 −2 Pa film after vacuum annealing, too. Figure 5͑a͒ shows the Co 2p 3/2 XAS and XMCD spectra of the P O2 =10 −2 Pa film before and after the annealing.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous XMCD measurements on a heteroepitaxial Zn 1−x Co x O thin film grown on Al 2 O 3 ͑0001͒ substrates, 17 we have concluded that the ferromagnetism comes from Co ions substituting the Zn site in ZnO, and proposed that nonferromagnetic Co ions are strongly coupled antiferromagnetically with each other from the linear magnetic-field ͑H͒ dependence and temperature ͑T͒ independence of XMCD. Sati et al 18 reported antiferromagnetic interaction in single crystalline Zn 1−x Co x O thin films with low Co concentration ͑x = 0.003-0.005͒ from magnetic and EPR measurements. On the other hand, there are some reports that the Co 3d electrons are not the origins of the ferromagnetism 19 or that metallic Co atoms contribute to the ferromagnetism.…”
Section: Introductionmentioning
confidence: 99%
“…23 Very recently, Iuşan et al 24 have shown that the magnetic exchange parameters calculated with LSDA+ U for Co doped ZnO are in good agreement with the magnetic measurements. 25 Considering the importance of Coulomb correlation, we have employed GGA+ U method for the description of TM-d states in the TM doped ZnO cluster. We have calculated the stability of the cluster on doping, the corresponding magnetic moments, and magnetic interactions between two TM ions.…”
Section: Resultsmentioning
confidence: 99%